2014
DOI: 10.13181/mji.v23i1.685
|View full text |Cite
|
Sign up to set email alerts
|

Serum levonorgestrel concentration and cervical mucus viscosity after six months of monoplant® implantation

Abstract: AbstrakLatar belakang: Penggunaan implan levonorgestrel sebagai metode kontrasepsi telah mengalami perubahan dari enam batang pada metode awal hingga dua batang pada metode terbaru dan telah terbukti efektif. Penelitian ini bertujuan untuk mengevaluasi efektifitas pemakaian satu batang implan (Monoplant®) dengan mengukur kadar levonorgestrel serum dan kualitas mukus serviks.Metode: Sebanyak 30 wanita sehat, usia 20-40 tahun, terbukti fertil, dilakukan pemasangan susuk levonorgestrel satu batang. Pemeriksaan ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…A similar trend was observed in a macaque efficacy study [53]. At the levels of LNG achieved in serum, contraceptive efficacy has been reported [65] in women. However it should be noted that Dusterberg et al, [73] reported inter-species related variations in (%) bioavailabilities and plasma half-lives of three different progestogens including LNG.…”
Section: 0 Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…A similar trend was observed in a macaque efficacy study [53]. At the levels of LNG achieved in serum, contraceptive efficacy has been reported [65] in women. However it should be noted that Dusterberg et al, [73] reported inter-species related variations in (%) bioavailabilities and plasma half-lives of three different progestogens including LNG.…”
Section: 0 Discussionsupporting
confidence: 84%
“…No LNG was detected in the MZC IVR group, as expected. The average LNG levels from the MZCL IVRs on the last day (d23) of use were 355 ± 88 pg/mL, level associated with contraceptive activity [64, 65]. Based on the PK profile, other PK parameters were computed as follows: AUC 48h - ∞ was 8.07 ng.d.…”
Section: 0 Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In emergency contraception, studies have shown that levonorgestrel works by preventing or delaying ovulation and impairing luteal function [ 13 – 15 ]. LNG may also increase the thickness of the cervical mucus or affect sperm migration and function in the genital tract, thereby preventing fertilization of an egg [ 16 ]. Some studies have found no effect of levonorgestrel on the endometrium, the quality of cervical mucus, nor the penetration of spermatozoa in the uterine cavity [ 17 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…e most commonly reported side effect is irregular menstrual bleeding which often causes users to discontinue implant use [14][15][16][17]. Changes in menstrual patterns such as amenorrhea, spotting, and prolonged menstruation are often complained of by implant users [18][19][20][21]. Other factors affecting menstrual patterns include breastfeeding and body mass index.…”
Section: Introductionmentioning
confidence: 99%